Analisis Penyelarasan Inovasi Perbankan Digital Bank Jago dengan Tujuan Pembangunan Berkelanjutan (2022–2024) - Indri Iswardhani (MENAWAN : Jurnal Riset dan Publikasi Ilmu Ekonomi, 2025)
This research aims to analyze the alignment of Bank Jago’s digital banking innovations with the Sustainable Development Goals (SDGs) during the 2022–2024 period. The method used is a qualitative descriptive analysis with a document study approach, which includes the Annual Report, Integrated Report, and Sustainability Report of Bank Jago over the past three years. The results of the study indicate that Bank Jago’s digital innovations are aligned with the five main dimensions of the SDGs: economic, social, governance, environmental, and partnership. From the economic perspective, digitalization has enhanced efficiency and financial performance through the growth of third-party funds and the expansion of access to digital services. In the social dimension, financial literacy programs, MSME financing, and digital zakat initiatives have strengthened financial inclusion among communities. The governance and environmental aspects demonstrate a commitment to transparency, energy efficiency, and green banking practices. Meanwhile, collaborations with fintech ecosystems and social institutions have reinforced sustainable partnerships. Overall, Bank Jago has implemented a digital transformation strategy aligned with the principles of Strategic Fit and Value Co-Creation, making digital innovation not only an instrument of economic growth but also a means to achieve sustainable development in Indonesia’s banking sector.